Multifunctional Ag/ZnO/chitosan ternary bio-nanocomposites synthesized via laser ablation with enhanced optical, antibacterial, and catalytic characteristics. (October 2022) - Ali, Heba; Ismail, A.M.; Menazea, A.A.
Abstract: Organic dyes and microorganisms in industrial wastewater have harmed both the environment and human health. Herein, Ag/ZnO/chitosan (Ag/ZnO/Cs) ternary bio-nanocomposites were prepared by anchoring Ag NPs to the ZnO/Cs matrix by the laser ablation method as multifunctional materials. The proposed strategy enables the growth of very fine Ag NPs (2–10 nm) with good dispersion, resulting in the synthesis of Ag/ZnO/Cs composites with antibacterial effectiveness, enhanced UV–visible barrier characteristics, and boosted catalytic reduction properties. The successful formation of nanomaterials (ZnO and Ag) was confirmed by XRD, UV–Vis, HRTEM, and FTIR. The optical studies anticipate that the synthesized Ag/ZnO/Cs films will provide significant photocatalytic capability. TGA confirmed that the composite film had improved thermal stability over the Cs film. Staphylococcus aureus, Bacillus subtilus, Escherichia coli, and Pseudomonas aeruginosa are used to study the antibacterial activity of various Ag/ZnO/Cs hybrids. The influence of Ag NPs on increasing the catalytic potential of nanocomposite films was investigated by methyl orange (MO) reduction. The mechanism of enhanced catalytic reduction activity owing to ZnO/Ag co-sensitization was also discussed. Finally, within 10 min Ag/ZnO/Cs exhibited 90 % removal efficiency after four cycles, demonstrating the efficiency and stability of the composite catalyst in reduction procedures. Graphical abstract: Unlabelled Image Highlights: The growth of very fine Ag NPs (2–10 nm) with good dispersion in Cs matrix. Ag/ZnO/Cs films have improved opacity and light barrier properties. The band gap shifted from 5.25 eV to 3.15 eV after sensitization with ZnO and Ag NPs. The antibacterial activity of Ag/ZnO/Cs composite is two times higher than pure Cs. Ag/ZnO/Cs demonstrated 90 % removal efficiency after 4 cycles in reduction procedures.